Nigeria : 2010; Article IV Consultation-Staff Report; Debt Sustainability Analysis; Informational Annex; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Nigeria. (IMF Staff Country Reports; Country Report ;, 2011)
In this study, economic growth and development of Nigeria after the crisis is discussed. Nigeria's economy is projected to grow by 7 percent in 2011. Near-term risks to growth mostly relate to domestic factors. Nigeria's strong external position and low debt helped mitigate the impact of the global financial crisis. Conflicting objectives of monetary policy and policy framework should focus more on price stability. Establishment of an asset management corporation to clean up the bank balance sheet is encouraged.